3x-10+6x-2=96

Simple and best practice solution for 3x-10+6x-2=96 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-10+6x-2=96 equation:



3x-10+6x-2=96
We move all terms to the left:
3x-10+6x-2-(96)=0
We add all the numbers together, and all the variables
9x-108=0
We move all terms containing x to the left, all other terms to the right
9x=108
x=108/9
x=12

See similar equations:

| 8(-8+3x)=-13+7x | | 2x+4=7x-2+7x-2 | | Y=5,000x+.8 | | 7(m-4)=6(m+12)-4m | | 4(3x+8)=-39+11 | | 2x-3+x-5=11 | | -5+3(3a+5)=25+4(2a-2) | | 3x-2+4x=18x | | 6y=-4y+10 | | 2/3x6=36 | | 3(y+1)=19-15y | | 6d+8=14+33d | | 9+5x=7x-11 | | 2x+12+2x+5=7x+1 | | 5-3(2-x)=4x-7 | | )9=-3/8r | | -28r=4r | | 3a-7=2(6a+5) | | -3(x+8)=33 | | -2(-2)c=8 | | 6(x-12)=2(11x-4) | | –15w−–16w−–15=11 | | x+7x+1=180 | | -(x-7)=11 | | 3x+7-5x=-13 | | y/3y=48 | | 1-3x=1-x | | (2b-6)/6=2/3 | | 5x-3(x-4)=-6+5-6 | | 8.52-11.8b=-18.4b-8.91 | | 7x–2=x–14 | | 2(4x−3)=4x−30 |

Equations solver categories